Dual Metal‐Assisted Defect Engineering towards High‐Performance Perovskite Solar Cells. (21st October 2022) - Zhang, Chengxi; Baktash, Ardeshir; Zhong, Jun‐Xing; Chen, Weijian; Bai, Yang; Hao, Mengmeng; Chen, Peng; He, Dongxu; Ding, Shanshan; Steele, Julian A.; Lin, Tongen; Lyu, Miaoqiang; et al.
Abstract: Perovskite solar cells (PSCs) have witnessed an unprecedentedly rapid development, especially in terms of power conversion efficiency (PCE). However, the solution‐processed perovskite films inevitably possess numerous crystallographic defects (e.g., halide vacancies), which has been shown to incur non‐radiative charge recombination and ion migration, thus limiting the enhancement of the PCE and stability of PSCs. Here, a novel dual metal (i.e., divalent and monovalent metal ions) modification strategy is reported for simultaneously reducing the defects, immobilizing the halide anions, and preventing ion loss from perovskite during post‐annealing process. Accordingly, this strategy significantly reduces non‐radiative recombination, enhancing the PCE by ≈12% and mitigating the current density‐voltage ( J – V)  hysteresis effect in resultant devices compared to undoped counterparts. As a result, a champion PCE exceeding 22% and a high open‐circuit voltage ( Voc ) of 1.16 V is obtained for dual metal ions‐modified PSCs. The optimized devices also exhibit extended lifespan upon the dual metal treatment. The study provides a new defect engineering strategy toward more efficient and stable perovskite photovoltaics. Abstract : A dual‐metal doping defect engineering strategy is developed to minimize non‐radiative recombination, mitigate hysteresis, improve efficiency with low voltage deficit and extended lifespan in perovskite solar cells.